Free radical scavenging activity of Eagle tea and their flavonoids - Qiong Meng; Zhengming Qian; Xiaoxiang Li; Deqiang Li; Weihua Huang; Jing Zhao; Shaoping Li (Elsevier, 2012)
In this study, an online HPLC-DAD-MS coupled with 2,2'-azinobis (3-ethylbenzthiazoline-6-sulfonic acid) diammonium salt (ABTS) assay was employed for evaluating free radical scavenging activity of Eagle tea and their active components. Twenty-three chromatographic peaks were detected, and nineteen components had free radical scavenging activity. Among them, eight compounds were identified as flavonoids (hyperin, isoquercitrin, quercitrin, quercetin, kaempferol), catechins, chlorogenic acid and epicatechin based on MS data and standard chromatographic characters.